Optimization of Service at Public Fuel Filling Stations (SPBU) Using Multiple Channel Single Phase Queue Model - Rianita Simamora; Rector Sianturi; Junarti Junarti; Gayus Simarmata (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2025)
Queues are a phenomenon that often occurs in people's lives, especially in the service industry such as what happens at the 14.211.207 Pematangsiantar gas station where the queue starts in the morning. One indicator is that customers have to queue for a long time to get fuel filling services at the gas station if left alone, it can cause customers to exit the system. So the queue problem must immediately be a priority to find a way out. This study aims to determine the level of optimal fuel filling system service and to determine the optimal or ideal fuel filling service system at the 14.211.07 Pematangsiantar gas station. The research method used in this study is applied research, namely research conducted to obtain information used to solve problems using quantitative methods to determine the level of optimal fuel filling system service at the gas station. Data collection was carried out by observing and recording the queues that occurred in the morning. The queue model used is Multiple Channel Single Phase with the First In First Out (FIFO) queue discipline. From the results of the calculation of the performance of the queue system at the 14,211,207 Pematangsiantar gas station, it was found that the service level with two or more gas stations was optimal, namely below 50%.